UMP Cares – Food for All Programme for students and the needy - UMP, PNC (2019)
The Islamic Centre and Human Development (PIMPIN) and MyGift Squad, Universiti Malaysia Pahang (UMP) organised a programme called ‘Food for All’ as part of the efforts to tackle issues involving some of the university students who often had to go hungry due to financial constraint.